Assessing the correlation between climate signals and monthly mean and extreme precipitation and discharge of Golestan Dam Watershed (2015)
Climate teleconnection signals are one of the main factors influencing the earth's climate oscillations in global and regional scales. In the present research, the effect of these signals on precipitation and discharge of Madarsoo Watershed at the upstream of Golestan Dam was investigated. For this purpose, three raingauges and hydrometric stations with respectively 40 and 38 years of daily rainfall and discharge data were selected. Pearson-correlation coefficient was used to consider the correlation between climate signals and monthly mean and extreme precipitation and discharge. The results showed strong correlation between monthly total precipitation of Tangrah and Tamer with Sea Level Pressure (SLP) of Caspian Sea with 7 and 9 months of lag, respectively, and Galikesh with Sea Surface Temperature (SST) of Caspian Sea with 9 months of lag. For monthly mean discharge of Tangrah and Galikesh, the maximum correlation was calculated for SLP of Caspian Sea with a lag of 9 months and Tamer with SST of Greenland with a lag of 7 months. For the extreme monthly data, very strong correlation was detected between the precipitations of all raingauges in June with Greenland SST with 8 months of lag. In contrast, for maximum monthly discharge of Tangrah and Galikesh hydrometric stations, the maximum correlation coefficients were calculated for SST of Black Sea with 4 months of lag in August and for Tamer with SLP of Caspian Sea with 4 months of lag in August. With regard to the results, the utilization of these signals, especially SLP and SST, is strongly suggested to predict the maximum and mean monthly precipitation and discharge over this region. ResumenLas señales de teleconexión atmosférica son uno de los factores principales que influencian las oscilaciones climáticas de la tierra a escala global y regional. En el presente estudio se investigan los efectos de estas señales en la precipitación y caudal de la cuenca hidrográfica Madarsoo, río arriba de la presa Golestan. Con este propósito se seleccionaron tres estaciones pluviométricas e hidrométricas con registros diarios de lluvia y caudal durante unas cuatro décadas. Se utilizó el coeficiente Pearson para considerar la correlación entre las señales climáticas y los índices medio y extremo mensual de precipitación y caudal. Los resultados muestran una fuerte correlación entre la precipitación total mensual de las estaciones Tangrah y Tamer con la Presión Barométrica a Nivel del Mar (SLP, inglés) en el mar Caspio, en un período de siete y nueve meses, respectivamente, y de la estación Galikesh con la Temperatura a Nivel del Mar (SST, inglés) en el Caspio durante nueve meses. Para la media mensual del caudal en Tangrah y Galikesh, la correlación máxima se calculó a través de la SLP del mar Caspio con un período de nueve meses, y la de Tamer con la SST del mar de Groenlandia en un lapso de siete meses. Para el índice extreme mensual se detectó una fuerte correlación entre las precipitaciones medidas en todos los pluviómetros en junio con la SST de Groenlandia en un período de ocho meses. En contraste, para el índice máximo mensual de caudal en las estaciones hidrométricas Tangrah y Galikesh se calcularon los coeficientes de correlación máxima para la SST del mar Negro en un lapso de cuatro meses en agosto y para la estación Tamer con la SLP del mar Caspio durante cuatro meses, también en Agosto. Con respecto a los resultados, se recomienda la utilización de estas señales, especialmente la SLP y la SST, para predecir los índices de precipitación y caudal medio y máximo en esta región.